The Encyclopedia of Physics - Rosen, Joe (New Dehli Viva Books, 2016)
The editors of this Encyclopedia, earlier editions of which met with international acclaim, have now provided a fully revised, expanded and updated third edition of this comprehensive reference work. In two volumes, 500 experts -- among them several Nobel laureates and numerous other scientific award winners -- offer a comprehensive and topical account of physics and the physical world. The volumes comprise more than 500 articles, which have either been completely updated or are altogether new, covering the latest terminology and techniques in physics, including atomic trapping and cooling, biophotonics, econophysics, the formation of stars and planets, quantum communication, space science and technology, and traffic flow. - Publisher
Includes Appendix, Illustrations and Index.
Keywords: Physics